Health care providers' and mothers' perceptions about the medicalization of female genital mutilation or cutting in Egypt: a cross-sectional qualitative study - Omaima El-Gibaly; Mirette Aziz; Salma Abou Hussein (BMC, 2019)
Abstract Background Female genital mutilation/cutting (FGM/C) is a traditional harmful practice that has been prevalent in Egypt for many years. The medicalization of FGM/C has been increasing significantly in Egypt making it the country with the highest rate of medicalization. In this qualitative study, we explored the drivers and motives behind why healthcare professionals perform FGM/C and why mothers rely on them to perform the practice on their daughters. Methods The study drew on a "mystery client" approach, coupled with in-depth interviews (IDIs) and focus group discussions (FGDs) with health care providers (i.e. physicians and nurses) and mothers. It was conducted in three geographic areas in Egypt: Cairo, Assiut and Al Gharbeya. Results Study findings suggest that parents who seek medicalized cutting often do so to minimize health risks while conforming to social expectations. Thus, the factors that support FGM/C overlap with the factors that support medicalization. For many mothers and healthcare providers, adherence to community customs and traditions was the most important motive to practice FGM/C. Also, the social construction of girls' well-being and bodily beauty makes FGM/C a perceived necessity which lays the ground for stigmatization against uncut girls. Finally, the language around FGM/C is being reframed by many healthcare providers as a cosmetic surgery. Such reframing may be one way for providers to overcome the law against FGM/C and market the operation to the clients. Conclusion These contradictions and contestations highlighted in this study among mothers and healthcare providers suggest that legal, moral and social norms that underpin FGM/C practice are not harmonized and would thus lead to a further rise in the medicalization of FGM/C. This also highlights the critical role that health providers can play in efforts to drive the abandonment of FGM/C in Egypt.